2013
DOI: 10.1080/09658211.2013.868907
|View full text |Cite
|
Sign up to set email alerts
|

Early memories in young adults from separated and non-separated families

Abstract: Two studies investigated the earliest memories of New Zealand European young adults (N = 80, Study 1 and N = 120, Study 2) from separated and non-separated families. Participants' earliest memories were assessed for age, for density (how far apart the memories were, Study 2) and for narrative coherence of the memories. Questionnaires were designed to investigate the role of changes in family structure, for example, in the number of adults in the participants' households and the timing of the parental separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 78 publications
2
20
0
Order By: Relevance
“…Nevertheless, greater involvement of the HPC in threat learning in ECA-exposed youths is consistent with the idea that HPC-mediated behaviors (such as context learning) might show accelerated development following stress. One study that seems to support this idea has shown that autobiographical memories, a hippocampaldependent phenomenon, emerge earlier in life following parental divorce (Artioli & Reese 2014). However, that study relied on retrospective reports of autobiographical memories, which are not always reliable, and was not examining the fear system per se.…”
Section: Disruption Of the Parent-child Dyadmentioning
confidence: 99%
“…Nevertheless, greater involvement of the HPC in threat learning in ECA-exposed youths is consistent with the idea that HPC-mediated behaviors (such as context learning) might show accelerated development following stress. One study that seems to support this idea has shown that autobiographical memories, a hippocampaldependent phenomenon, emerge earlier in life following parental divorce (Artioli & Reese 2014). However, that study relied on retrospective reports of autobiographical memories, which are not always reliable, and was not examining the fear system per se.…”
Section: Disruption Of the Parent-child Dyadmentioning
confidence: 99%
“…The separation per se could be used as a signpost to identify early personal memories. Moreover, children from early-separated families are more likely to grow up in extended-family settings, with a greater number of adults in the child-rearing environment (e.g., grandparents and step-parents), compared to children from later-separated families, who are more likely to grow up in sole-parent families (Artioli & Reese, 2013). Early parental separation could serve as a benchmark for early memories and could simultaneously increase the richness of the early reminiscing environment through the addition of new adults to the household, both of which would serve to lower the offset of childhood amnesia (cf.…”
mentioning
confidence: 99%
“…Early childhood amnesia is considered by some researchers as a universal phenomenon (Freud, 2014;Rubin, 2006;Tustin & Hayne, 2010) and seems to identify with a limited number of autobiographical memories, starting with the first years of life (Bauer & Larkina, 2013;Bauer, Tasdemir-Ozdes, & Larkina, 2014). Young adults who have lived a painful separation experience of their parents before the age of 7 have earlier autobiographical memories as compared to young adults whose parents separated later or were not separated at all (Artioli & Reese, 2014). Those individuals who were raised in families having many members appear to have memories with small time-windows between them (Artioli et al, 2012;Artioli & Reese, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Young adults who have lived a painful separation experience of their parents before the age of 7 have earlier autobiographical memories as compared to young adults whose parents separated later or were not separated at all (Artioli & Reese, 2014). Those individuals who were raised in families having many members appear to have memories with small time-windows between them (Artioli et al, 2012;Artioli & Reese, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation